Parametric instability analysis of laminated composite plate subject to various types of non-uniform periodic in-plane edge load - Adhikari, Balakrishna; Singh, B.N. (Applied mathematics and computation, 2020)
In this paper, the dynamic instability behavior of laminated composite plate structure is predicted under different types of non-uniform harmonic edge compressive loading. A nine degree of freedom (DOF) type polynomial based higher order shear deformation theory (HSDT) is considered for the finite element discretization of the plate. The application of non-uniform harmonic in-plane edge load causes the in-plane stress variation to be non-uniform. Hence, the in-plane stresses need to be evaluated, prior to the instability analysis, for the evaluation of critical buckling load. These in-plane stresses are computed using in-plane stress analysis approach using finite element method. The differential equations of motion of the system are turned into a set of ordinary differential equations (Mathieu type equations) and solved as a general eigenvalue problem as per the procedure suggested by Bolotin. The accuracy and flexibility of the present model are validated by contrasting the present outcomes and the available solution. Further, the impact various parameters like span-thickness ratio, aspect ratio, diverse in edge constraints, different types of non-uniform periodic edge load, etc. on the dynamic instability behavior of the laminated composite plate are contemplated.